Black cohosh efficacy and safety for menopausal symptoms. The Spanish Menopause Society statement. (4th May 2022) - Castelo-Branco, Camil; Navarro, Concepción; Beltrán, Estanislao; Losa, Fernando; Camacho, Marta; ,
Abstract: Objective: The increasing interest in Western countries regarding phytotherapy use to treat menopause-related symptoms has led the Spanish Menopause Society (AEEM) to update its position statement performed in 2009 on the role of black cohosh ( Cimicifuga racemosa ) for the treatment of menopausal symptoms. Material and methods: A panel of experts from both clinical and research backgrounds were assembled to investigate the best available evidence. Selected studies were obtained by an electronic search, including the Internet search engines MEDLINE-Pubmed (1997–December 2021) and the Cochrane Controlled Trials Register. Results: Most of the well-designed studies published in recent years have been conducted with the isopropanolic extract of black cohosh/ C. racemosa . The most common dose is 40 mg/day capable of achieving a significant reduction in hot flushes (particularly in women with intense hot flushes) and an improvement in mood. Used at the recommended doses, C. racemose produces no significant adverse reactions. Conclusion: Black cohosh is an effective and safe treatment option for the relieving of vasomotor symptoms. Finally, further clinical trials with sufficient patient enrollment and longer study follow-up are needed.